Ubiquity in Time and Architectural Space - Ivan Segura Lara (Architecture Image Studies Scientific Journal)
Digital technology has produced radical changes in behavior. Through smartphones, we no longer live in the here and now that makes each moment a present outside of time. We move into states of alternative consciousness, which are states of concentration and states of distraction. We are here and there, without being fully anywhere. This notion of space has been disrupted by the irruption of virtual realities, with tools that allow immersion in simulated realities that have the potential to transform faster than what our senses could encompass with the real body. Architectural designers have found tools for drawing and immersion in imaginary spaces that transform in real time according to the needs of a clientele or creation projects. This is how today we can, through virtual images, simulate architectural spaces to represent work spaces. This potential of the virtual gives rise to activities such as those of the so-called « digital nomads, who are professionals who break the barriers of presence in sectors such as technology, programming, digital marketing, design or consulting. » We will show the other side of this development of the virtual world by studying the architectural setting of the city of Wuhan.